MUTU PELAYANAN KESEHATAN PESERTA ASKES DITINJAU DARI SEGI PELAYANAN PRIMA PADA UNIT RAWAT INAP RUMAH SAKIT GRAHA JUANDA - Kurniati Nawangwulan; Zulaika; Yusnita Yusfik (Journal of Hospital Administration and Management (JHAM), 2026)
Efforts to provide good health services to speed up the healing process of illnesses suffered are everyone's hope and human right. The aim of the research is to determine the description of the quality of health services for Askes participants in terms of Responsiveness, Assurance, and Empathy Based on Education, Years of Service, and Incentives for health workers at Hospital Graha Juanda. This type of research is observational with a descriptive approach to obtain an overview of quality Health services are reviewed in terms of excellent service at Hospital Graha Juanda. The results showed that 89.2% of the 37 health workers who said they received incentives provided good quality service to health insurance patients, while 41.4% of the 29 health workers who said they did not receive incentives provided good quality service. The conclusion is that there are 83.0% of health workers who have a D3 education level and provide excellent quality service to health insurance patients and 89.2% of health workers who receive incentives and provide good quality service to health insurance patients are 89.2%.